2018
DOI: 10.23950/1812-2892-jcmk-00563
|View full text |Cite
|
Sign up to set email alerts
|

Hematological dynamics following the co-administration of Resveratrol and Cisplatin in Sprague–Dawley rats.

Abstract: Background: Cisplatin, a platinum-based chemotherapy agent, is used in the effective treatment of a wide range of malignant cancers. Resveratrol, a polyphenolic plant-derived compound, has been shown to have several biological effects including protecting the body against several forms of damages.Objective: This study assessed the effects of cisplatin and supplementation with resveratrol on some hematological parameters in Sprague-Dawley rats.Material and Methods: Forty-five adult female Sprague-Dawley rats, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We also observed that the total WBC count returned to normal (i.e., pre-CP levels) around day 6 (144 h) after CP treatment, which aligns with the previous study by Nowrousian and Schmidt [ 30 ]. This increase in the WBCs on day 6 might be due to infection and inflammation during CP administration and CP metabolism in the rats [ 9 , 31 ]. While similar effects were observed in both VAC-treated groups, the extent of decrease in the total WBCs on day 3 in the VAC-350 group was lesser than that in the VAC-650 group, indicating that treatment with 350 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the total WBC count returned to normal (i.e., pre-CP levels) around day 6 (144 h) after CP treatment, which aligns with the previous study by Nowrousian and Schmidt [ 30 ]. This increase in the WBCs on day 6 might be due to infection and inflammation during CP administration and CP metabolism in the rats [ 9 , 31 ]. While similar effects were observed in both VAC-treated groups, the extent of decrease in the total WBCs on day 3 in the VAC-350 group was lesser than that in the VAC-650 group, indicating that treatment with 350 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%